Ecommerce Adoption : An Empirical Investigation in Wooden Handicraft SMEs of Saharanpur, Uttar Pradesh - Yadav, Rohit; Mahara, Tripti (Prabandhan: Indian Journal of Management, 2018)
Ecommerce has brought numerous changes to organizations and their businesses along with helping them to achieve excellence in different countries. This study empirically investigated the factors affecting ecommerce adoption by small and medium - sized enterprises of wooden handicrafts located in Saharanpur, Uttar Pradesh. It was motivated by the fact that even though the handicraft sector plays a vital role in the Indian economy in terms of exports and employment, it has not adopted ecommerce as one of the prominent sales channels for their products. The technological, organizational, environmental, and strategy model based on the TOE framework was proposed in this research. This study was conducted with 163 sampled SMEs to identify various factors that influenced ecommerce adoption. The findings revealed that organizational, technological, and strategy factors significantly contributed to initial ecommerce adoption in the wooden handicraft SMEs of Saharanpur. The study can be further extended to other handicraft products manufactured in different parts to the country to understand the factors affecting ecommerce adoption.